Pengaruh Media Audio Visual terhadap Kemampuan Teknik Dasar Smash Permainan Bulu Tangkis Siswa Sekolah Menengah Kejuruan - Windary Windary; Ega Trisna Rahayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to determine the effect of audiovisual media on improving the ability to perform basic smash techniques in badminton. This study uses a one-group pretest-posttest design. This research implements audiovisual media in learning basic smash techniques. The subjects used in the study were Vocational High School students with 18 people consisting of 7 students and 11 students with an average age of 16 years. Data collection techniques used pre-test together with post-test, analyzed using t-test. This study indicates an increase in using audiovisual media, namely the with the Shapiro-Wilk test > 0.05; it can be interpreted that the data is usually distributed and the results of the calculation of the paired sample test obtained sig. (2-tailed) of 0.00 where if sig. (2-tailed) <0.05, it is stated that there is a significant effect. The conclusion is that audiovisual media is very influential in improving the ability to perform basic smash techniques in badminton. Keywords: Audio Visual Media, Smash Basic Techniques. Vocational High School Students